Middle cerebral artery stenosis is associated with the increased risk of intracerebral hemorrhage in Chinese: A retrospective study - Shen, Lin; Zhou, Huchuan; Wei, Fei; Shuai, Jie (Medicine (Baltimore), 2019)
Intracerebral hemorrhage (ICH) is a major cause of morbidity and mortality throughout the world. It is reported that the incidence of deep ICH and intracranial artery stenosis (ICAS) are higher in Asian countries. Thus, there are concerns regarding a potential relationship between ICAS and ICH. This study was aimed to investigate this potential relationship between intracranial artery (middle cerebral artery, MCA) stenosis and ICH in the lateral lenticulostriate artery (LLA) territory in Chinese. Totally, 973 in-hospital subjects were retrospectively enrolled including subjects with the diagnosis of ICH, acute ischemic stroke (IS), and prior IS and subjects without cerebral diseases. These subjects were divided into four groups: ICH, acute IS, prior IS, and normal group (without cerebral diseases). Multiple logistic regression analysis showed that severe MCA stenosis was associated with the increased risk of ICH (OR = 5.070) and acute IS (OR = 5.406) in the LLA territory. The moderate MCA stenosis was associated with the increased risk of ICH (OR = 9.899) and was not associated with acute IS in the LLA territory. The increased perfusion pressure to the LLA may be the cause. In conclusion, MCA stenosis, especially moderate MCA stenosis, is associated with ICH in the LLA territory in Chinese.